STUDI KOMPARATIF USAHATANI TEBU RAKYAT KEMITRAAN (TRK) DAN TEBU RAKYAT MANDIRI (TRM) DENGAN PABRIK GULA MADUKISMO - Masyhuri Masyhuri; Hani Perwitasari; Hadfina Nurjannah (Universitas Sebelas Maret, 2016)
Plantation crops that have an important role in Daerah Istimewa Yogyakarta economy is sugar cane. One of developing sugarcane factory is Madukismo, located in Bantul district. This study aims to know partnership between Madukismo factory and farmers, namely Tebu Rakyat Kemitraan (TK) dan Tebu Rakyat Mandiri (TRM), compare profit, and analyze their feasibility. A sample size of 29 TRK and TRM farmers was obtained both purposive and simple random sampling techniques. T test is used to compare their profit and feasibility. The results show that TRM farming is more profitable and feasible that TRK farming.